The Use of Educational Games in High School Chemistry Learning in West Java Province - Silvia Fransiska Tarigan; Wiji Wiji (Postgraduate, University of Mataram, 2023)
The implementation of games in chemistry classes has provided an interesting and alternative teaching method and allows students to learn in a more entertaining way compared to traditional learning process. The game-based learning approach is divided into three approaches, namely game-based learning or educational games, gamification, and game-assisted learning. Many chemistry games have been constructed in recent years to review and strengthen various chemistry topics; therefore, it is expected that Chemistry teachers in high schools in Indonesia, especially in West Java province implement educational games in the learning process. For that reason, it is necessary to perceive an overview of the use of educational games in Chemistry learning in secondary schools in West Java province. Survey research was carried out using a random sampling technique. There were 99 chemistry teachers from 91 high schools spread across the province of West Java who voluntarily participated in the online survey. The result of the analysis obtained that 35% of chemistry teachers in the province of West Java have implemented gamification and learning using game assistance. On the contrary, game-based learning has never been implemented in Chemistry learning process in secondary schools in West Java province